2017
DOI: 10.1016/j.msea.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Processing, microstructural evolution and strength properties of in-situ magnesium matrix composites containing nano-sized polymer derived SiCNO particles

Abstract: In-situ Mg matrix composites are fabricated by combining both liquid-and solid-state processing routes. Firstly, liquid polymer was injected into the molten Mg at a temperature of 800 o C to initiate pyrolysis. In-situ pyrolysis aids in the conversion of liquid polymer into sub-micron sized SiCNO particles (mean particle size in the range of 0.5-1 m) and Mg 2 Si particles. Most of the polymer derived SiCNO particles were pushed by the solidification front and as a result segregated at the grain boundaries of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…During in-situ pyrolysis, the chance of forming (Fig 9(d) Table 3 [13]. The properties and parameters which are used for calculating the various strengthening modes are provided in Table. 4 and Table. 5.…”
Section: Ae44 Matrix Compositementioning
confidence: 99%
See 1 more Smart Citation
“…During in-situ pyrolysis, the chance of forming (Fig 9(d) Table 3 [13]. The properties and parameters which are used for calculating the various strengthening modes are provided in Table. 4 and Table. 5.…”
Section: Ae44 Matrix Compositementioning
confidence: 99%
“…The most common numerical models to predict the yield strength of particulate MMCs are as follows [13,32] strengthening mechanisms which act unevenly throughout the matrix by least-square approximation. Sanaty-Zadeh et al [32] reported that the modified Clyne method can predict the yield strength more precisely than any other methods after comparing the various numerical models for the particulate MMCs.…”
Section: Verification Of the Numerical Modelsmentioning
confidence: 99%
“…reactions between principal alloy and the additives [46][47][48][49][50]. The type and number of additives are chosen based on final formulation of the matrix and volume fraction of the reinforcement.…”
Section: In-situ Casting Processingmentioning
confidence: 99%
“…Chelliah et al [46] synthesized magnesium-polymeric derived ceramic (PDC) silicon carbonitride (SiCNO) nano composite by liquid pyrolysis using stir casting technique. The liquid poly (urea-methyl-vinyl) silazane (PUVMS) was used to formulate magnesium nano-composite.…”
Section: In-situ Casting Processingmentioning
confidence: 99%
“…To date, PDCs are mainly classified as binary systems (eg, SiC, Si 3 N 4 , and BN), tertiary system (eg, SiCN, SiCO) and quaternary systems (eg, SiBCN, SiBCO, SiAlCO, and SiCNO), which is based on the number of constituent elements or phases in the final ceramic. Among these various PDCs systems, the Si‐based quaternary ones often possess the free carbon, stable Si–C bonds and overall disordered ceramic structure which make them higher in resistance to oxidation and hot corrosion.…”
Section: Introductionmentioning
confidence: 99%